Bad Faith Intersubjectivity: The phantom-subjective image in virtual reality contemporary art - Messham-Muir, Kit (2018)
In 1996, the early days of Virtual Reality, Lev Manovich contemplated the aesthetics of virtual worlds, saying ‘If you want to experience cyberspace of the future today, visit… Los Angeles. The city offers a precise model for the virtual world. There is no center, no hint of any kind of centralized organization, no traces of the hierarchy essential to traditional cities.’ 1 Twenty years later, Shaun Gladwell, contemporary artist and member of the Bad Faith VR collective created AR15 Field Strip, a 360-degree video set in a suburban garage in Los Angeles, depicting a blindfolded man, kneeling on the concrete floor as if in prayer, as he field strips an AR15 assault rifle – the type of firearm used in the 2016 Orlando nightclub massacre. Fixed to a point in front of him, we are given vision of confinement, dislocation and threat. In the context of gun violence in America, Gladwell gives a sinister twist to Manovich’s vision of VR in LA. AR15 Field Strip places the viewer in a point of view without subjectivity, in what Haran Farocki terms a ‘phantom-subjective image’, ‘taken from a position that a human cannot normally occupy’.2 Through Gladwell’s AR15 Field Strip, this paper explores some fundamental questions around VR in contemporary art today and its radical phenomenology of narratology and intersubjectivity.